Bond Markets As Conduits for Capital Flows : How Does Asia Compare? - Luengnaruemitchai, Pipat (IMF Working Papers; Working Paper ;, 2006)
We use data on the extent to which residents of one country hold the bonds of issuers resident in another as a measure of financial integration or interrelatedness, asking how Asia compares with Europe and Latin America and with the base case in which the purchaser and issuer of the bonds reside in different regions. Not surprisingly, we find that Europe is more financially integrated than other regions. Asia, more interestingly, already seems to have made more progress on this front than Latin America and other parts of the world. The contrast with Latin America is largely explained by stronger creditor and investor rights, better contract enforcement, and greater transparency, all of which are conducive to foreign participation in local markets and to intraregional cross holdings of Asian bonds generally. Further results based on a limited sample suggest that one factor holding back investment in foreign bonds in East Asia may be limited geographical diversification by mutual funds, in turn reflecting a dearth of appropriate assets. Asian Bond Fund 2, by creating a passively managed portfolio of local currency bonds potentially attractive to mutual fund managers and investors, may help to relax this constraint.